Prediction of Pharmacokinetics of Valeric Acid: Alternative Tool to Minimize Animal Studies - Kumari, Bindu; Singh, Dhananjay Kumar; Singh, Ravi Bhushan; Singh, Gireesh Kumar (Current Drug Metabolism, 2025)
BackgroundThe use of computer-aided toxicity and Pharmacokinetic (PK) prediction studies are of significant interest to pharmaceutical industries as a complementary approach to traditional experimental methods in predicting potential drug candidates.MethodsIn the present study, in-silico pharmacokinetic properties (ADME), drug-likeness, and toxicity profiles of valeric acid were examined using SwissADME and ADMETlab web tools.ResultsThe drug-likeness prediction results revealed that valeric acid adheres to the Lipinski rule, Pfizer rule, and GlaxoSmithKline (GSK) rule. From a pharmacokinetic perspective, valeric acid is anticipated to have the best absorption profile including cell permeability and bioavailability. Plasma Protein Binding (PPB) and Blood–Brain Barrier (BBB) permeability may have a positive effect on Central Nervous System modulating (CNS). There is a minimal chance of it being a substrate for cytochrome P2D6 (CYP). Except for a “very slight risk” for eye corrosion and eye irritation, none of the well-known toxicities in valeric acid were anticipated, which was compatible with wet-lab data. The molecule possesses no environmental hazard as analyzed with common indicators such as bio-concentration factor and LC50 for fathead minnow and daphnia magna. The toxicity parameters identified valeric acid as nontoxic to androgen receptors, antioxidant response element, mitochondrial membrane receptor, heat shock element, and tumor suppressor protein (p53), except Peroxisome Proliferator-Activated Receptor- gamma (PPAR-γ) was found to be medium toxicity. However, no toxicophores were found out of seven parameters.ConclusionOverall, the ADMETLab evaluated that valeric acid has favorable pharmacokinetic and drug-likeness profiles, making it a promising drug candidate for new drug development.
Keywords: pharmacokinetics